KUALIFIKASI PENGGUNAAN SENJATA KIMIA PADA KONFLIK BERSENJATA DI SURIAH DARI PERSPEKTIF HUKUM HUMANITER INTERNASIONAL: QUALIFICATION OF CHEMICAL WEAPONS IN ARMED CONFLICT IN SYRIA FROM THE PERSPECTIVE OF INTERNATIONAL HUMANITARIAN LAW - Fajwa, R. Halya Zayna; Wibowo, Aji (Fakultas Hukum Universitas Trisakti, 2024)
The conflict in Syria is part of the series of Arab revolutions that occurred in 2011 due to opposition to the regime of President Bashar al-Assad, evolving into armed rebellion. The conflict reached its peak when battles involving chemical weapons were discovered in Ghouta in August 2013, resulting in numerous casualties. This has qualified as war crimes and serious violations from the perspective of international humanitarian law. This research is a literature study using data analysis methods. Based on the data obtained, the use of chemical weapons in this warfare has violated the rules of the Organization for the Prohibition of Chemical Weapons and international humanitarian law agreements.